The Effects of Information Choice and Information Use in Analysts' Predictions of Municipal Bond Rating Changes. - Lewis, Barry L.; Patton, James M.; Green, Sharon L. (The Accounting Review, 1988)
Abstract The research reported here investigates the effects of information choice and information use on the quality of municipal financial analysts' predictions concerning changes in the general obligation bond ratings of cities. Analysts were given a menu from which they chose information; a statistical model of bond rating changes was constructed using the same information. Analysts predicted bond rating changes using either their self-selected information or information selected by the statistical model. Although previous research concluded that information choice was the main factor in humans' sub-optimal prediction achievement, the results in this study show that humans performed about as well as statistical models in a validation sample. Previous research was reinterpreted in light of the current results.